Calidad del servicio en la gerencia regional de transportes y comunicaciones percibido por el usuario, Trujillo. setiembre – noviembre 2014 - Rivas Sanjinez, Cesar Joel (2014)
This present project had like an objective determine how is the quality of the service perceived by the users of the Regional Management of Transport and Communications, this Investigation has been based in a descriptive transverse study. The model poll used like an instrument was SERVPERF, to measure quality of the perceived service. It has 5 dimensions (Tangibility, trustworthy, Capacity to respond, guarantee and empathy) and a systematic sample of 187 users. The statistical analysis was divided in two parts, the first part is about Evaluation of the variable’s dimension, quality of the service, following the model of the SERVPERF methodology. It has been determined that the quality of service perceived by the users in the Regional Management of Transport and Communications is regular with 78%._x000D_ The second statistical analysis has like a reference to multivariate analysis. Through the Dendrogram obtained were classsified into 4 clases as: Class 1 named class satisfied users in the dimensions of guarantee and tangibility, which is comprised of 85% of user. Class2 named class totally unsatisfied users in the dimensions of tangibility, which is comprised of 2.77% of user. Class 3 named class satisfied users in the dimensions of guarantee and Capacity to respond, which is comprised of 8.02% of user. Class 4 named class totally satisfied users in the dimensions of guarantee and empathy, which is comprised of 3.75% of user. According the factor analysis of multiple correspondence obtained in the dimension 1 (left side), we can say that the male users of 18 – 27 years old and 28- 37 years old have a good level of quality in Procedure of Recategorisation ,duplicate and revalidation._x000D_ In the dimension 2 (right side), we can say that the female users of 38– 47 years old and more of 48 years old have a bad and regular level of quality in Procedure to obtein their driver’s license